2002
DOI: 10.1037/0022-0663.94.4.820
|View full text |Cite
|
Sign up to set email alerts
|

Hope and academic success in college.

Abstract: A cognitive, motivational theory is introduced to the educational research community. Hope theory integrates the conceptualization of goals, along with the strategies to achieve those goals (pathways), and the motivation to pursue those goals (agency). In a 6-year longitudinal study, individual differences in hope, as measured by the Hope Scale (C. R. Snyder et al., 1991) scores of entering college freshmen, predicted better overall grade point averages even after controlling for variance related to entrance e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
379
4
15

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 555 publications
(417 citation statements)
references
References 58 publications
19
379
4
15
Order By: Relevance
“…In contrast, low hope students tend to adopt pessimistic attitudes that negatively affect subsequent activities (Snyder et al, 1996). Research by Duckworth (2016) also indicates that the concept of grit, which refers to the passion, perseverance and sustained self-control to pursue personally relevant and long-term goals, is related to the concept of hope.…”
Section: Discussion: 'Hanging In There'mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, low hope students tend to adopt pessimistic attitudes that negatively affect subsequent activities (Snyder et al, 1996). Research by Duckworth (2016) also indicates that the concept of grit, which refers to the passion, perseverance and sustained self-control to pursue personally relevant and long-term goals, is related to the concept of hope.…”
Section: Discussion: 'Hanging In There'mentioning
confidence: 99%
“…Snyder and colleagues suggest that high hope students tend to draw on past experiences, regardless of whether goals were achieved or not, as diagnostic feedback to inform subsequent actions and plans (Snyder et al, 1996). In contrast, low hope students tend to adopt pessimistic attitudes that negatively affect subsequent activities (Snyder et al, 1996).…”
Section: Discussion: 'Hanging In There'mentioning
confidence: 99%
“…Those with high hope will have the ability to set appropriate goals and find alternative paths of action to obtain desired outcomes. Hope has been positively associated with academic achievement (Snyder, Wiklund, & Cheavens, 1999), athletic performance (Curry & Snyder, 2000), preventing and recovering from physical illness (Irving, Snyder, & Crowson, 1998;Snyder, Feldman, Taylor, Schroeder, & Adams, 2000), coping with disability (Elliott, Witty, Herrick, & Hoffman, 1991), and psychological adjustment (Snyder, Cheavens, & Michael, 1999). More specific to this study, in a two-staged study of POB constructs, Youssef and Luthans (2007) found significant positive relationships between hope and employee performance, job satisfaction, and happiness.…”
Section: The Hope Capacitymentioning
confidence: 99%
“…That means that hopeful individuals are looking for something positive in a variety of conditions. Also, some researches have suggested that optimism is predominately related to agency hope and that hope pathways has unique contribution and beyond what was affected by optimism (see Snyder et al, 2002).…”
Section: Attributions and Emotions For Academic Achievementmentioning
confidence: 99%